1987
DOI: 10.1002/bbpc.19870910411
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination of adsorbates on single crystal electrodes with X‐ray standing waves

Abstract: Adsorption / Electrochemistry / Interfaces / Metals 1 Spectroscopy, X-ray TI submonolayers were deposited from an aqueous electrolyte on a Cu(l11) surface. The electrodes were studied inside and outsidc the electrolyte with standing X-ray wave fields. These measurements allow to determine the fraction and the position of TI atoms which occupy adsorption sites coherently relative to the bulk diffraction planes. The results show that the method can be applied to ex-situ as well as in-situ structure studies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Submonolayers of Cu deposited from an acidic solution of CuSO 4 at cathodic potentials adsorb predominantly in substitutional positions on the GaAs͑001͒ electrode. Part of the Cu, about 0.5 ML for n-type GaAs but only Ϸ0.05 ML for p-type GaAs, diffuse a few nm into the bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Submonolayers of Cu deposited from an acidic solution of CuSO 4 at cathodic potentials adsorb predominantly in substitutional positions on the GaAs͑001͒ electrode. Part of the Cu, about 0.5 ML for n-type GaAs but only Ϸ0.05 ML for p-type GaAs, diffuse a few nm into the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Later, surface x-ray diffraction 5 was successfully employed, 6 yielding detailed information about the interface structure, the structure of adsorbates, and potential-dependent structural processes of clean metal electrode surfaces. 7 Comparably little work has been done using semiconductor electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that oxygen containing species might be present on the surface of copper throughout the double layer charging region, including at the PZC, even though there is not evidence of its presence in the voltammetry. 69 Support for this conclusion came from dosing the clean Cu(lll) surface in UHV with increasing exposures to oxygen. The resulting oxygen containing surface gives an SH response which is more similar to that obtained in the electrochemical cell.…”
Section: Native Surface Studiesmentioning
confidence: 77%
“…It is interesting in retrospect to note that under their experimental conditions which included much care to reduce the presence of oxygen in solution, the thallium free surface displayed a rotational anisotropy similar to what Bradley et al 23 later obtained for oxygen dosed Cu(lll) in UHV. X-ray grazing incidence data by Materlin et al 69 also suggests that thallium grows on the surface of Cu(lll) in a disordered manner, largely due to the difficulty in producing an oxygen free substrate during electrodeposition in their grazing incidence cell. Later studies from this laboratory 23 ' 71 in which the electrolytes used and the surface preparation lead to an SH rotational anisotropy closer to that of clean Cu(lll) in UHV resulted in an SH anisotropy indicative of a relatively ordered overlayer growth on the surface.…”
Section: Underpotential Deposition Of Metallic Overlayersmentioning
confidence: 93%
“…Conventional XSW are generated using dynamical Bragg reflection [ 1-31 from perfect single crystals [4][5][6][7][8][9][10]. In this case the periodicity of the standing wave field is equivalent to the d-spacing of the (hkl) diffracting planes and, thus, this technique is a precise tool (± 1% of the d-spacing)[51 for measuring bond-lengths between adsorbate atoms and surface/bulk lattice positions over the range of 1 to 4A (i.e.…”
Section: Introductionmentioning
confidence: 99%